Massively parallel sequencing data of 31 autosomal STR loci obtained using the Precision ID GlobalFiler NGS STR Panel v2 for 82 Japanese population samples. (September 2022) - Kitayama, Tetsushi; Kiesler, Kevin M.; Fukagawa, Takashi; Watahiki, Haruhiko; Mita, Yusuke; Fujii, Koji; Sekiguchi, Kazumasa; Vallone, Peter M.; Mizuno, Natsuko
Highlights: Allele frequencies of 31 STR loci were obtained from 82 Japanese using Massively parallel sequencing. The same samples were genotyped using Capillary electrophoresis. Genotypes determined by Massively parallel sequencing and Capillary electrophoresis were 99.6% concordant. Discrepancies were only observed at D2S441 locus. Abstract: Allele frequencies for 31 autosomal short tandem repeat (STR) loci (CSF1PO, D10S1248, D12ATA63, D12S391, D13S317, D14S1434, D16S539, D18S51, D19S433, D1S1656, D1S1677, D21S11, D22S1045, D2S1338, D2S1776, D2S441, D3S1358, D3S4529, D4S2408, D5S2800, D5S818, D6S1043, D6S474, D7S820, D8S1179, FGA, Penta D, Penta E, TH01, TPOX, and vWA) were obtained using Precision ID GlobalFiler NGS STR Panel v2 from 82 unrelated individuals sampled from the Japanese population. Autosomal STR alleles designated by NGS and conventional capillary electrophoresis were found to be concordant except at D2S441 allele 9.